Pemahaman Nilai-nilai Bela Negara Generasi Muda Dalam Mnghadapi Informasi Di Era Digital - Yulnelly, Yulnelly; Setiyawati, Marina Ery (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
UPN “Veteran” Jakarta is one of 3 (three) State Universities (PTN) which initiallyhad the status of a Private Universities (PTS) until 2014 changed its status to PTN with thecharacteristics of State Defense. Defending the State is the effort of ev ery citizen inmaintaining the integrity of his country where this situation is realized, among others, by anattitude of love for the homeland and being willing to sacrifice. Along with advances in thefield of information technology, it is very easy and fast to get information from varioussocial media, so a wise attitude is needed in sorting information. Based on this, a researchwas conducted with the title Understanding the Values of State Defense of the YoungGeneration in Facing Information in the Digital Age. This study aims to find out and get anoverview of the younger generation regarding Bela values in the digital era. The methodused to obtain data and information by using a questionnaire as an instrument of datacollection from a predetermined sample that can represent the population. The researchapproach is quantitative research with descriptive research methods, namely all informationor data presented in the form of numbers and data analysis is carried out to obtainconclusions. The results obtained this study are that there is still an inappropriateunderstanding of the concept of Defending the State and there are still young people whoare not wise in using social media in the digital era